The case study on learning experiences of successful dyslexics - Stephannie, Maicheal. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study was conducted to explore the learning experiences of successful dyslexics from childhood till adult. It is based on the experiences and feeling for being dyslexic,parental support, and peers support in their learning. Various coping mechanism were used when they faced problems in their learning process from childhood till adult. A total of four people with dyslexia are selected as the respondents for this study. The respondents experienced many things in their life and faced many problems to cope with their dyslexia. They are not ashamed of themselves but they are so proud to be dyslexics and become successful.They get support from their family and peers. But some parents do not know that their children are dyslexic and some of their friends are underestimating them.The findings also uncover skills and knowledge that dyslexic learned through their life to be successful.